2022
DOI: 10.1071/zo22014
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the hatching success of artificially incubated eggs for use in a conservation program for the western saw-shelled turtle (

Abstract: Artificial incubation of eggs and the release of hatchlings into the wild is a common conservation intervention designed to augment threatened turtle populations. We investigate a range of incubation temperatures to establish an optimal temperature for maximum hatching success of western saw-shelled turtle (Myuchelys bellii) eggs. We report on the influence of incubation temperature on incubation duration and hatching success and describe two experimental incubation methods which, for the same incubation tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…To balance these two considerations, electric fences can be erected before the onset of nesting, left in place until eggs have hatched, and hatchling turtles have emerged, and then disassembled or completely removed to permit grazing. Incubating M. bellii eggs at lower temperatures extends incubation duration (Streeting et al, 2022) and therefore wet conditions and low temperatures will extend the period of time that fences are required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To balance these two considerations, electric fences can be erected before the onset of nesting, left in place until eggs have hatched, and hatchling turtles have emerged, and then disassembled or completely removed to permit grazing. Incubating M. bellii eggs at lower temperatures extends incubation duration (Streeting et al, 2022) and therefore wet conditions and low temperatures will extend the period of time that fences are required.…”
Section: Discussionmentioning
confidence: 99%
“…Our study was part of the 'Turtles Forever' conservation programme for M. bellii (Streeting et al, 2022), and we individually protected every intact nest that we found. Our study demonstrated that in the absence of protection, a very high proportion of M. bellii nests is preyed on by foxes.…”
Section: Implications For Conservation Managementmentioning
confidence: 99%
“…The collaboration has enabled national priorities to be set for E. macrurus and ensured that findings are incorporated into local water resource planning and strategic development throughout the Mary River catchment. The advent of similar collaborative community‐researcher conservation projects, such as the ‘1 Million Turtles’ (http://1millionturtles.com) and the ‘Turtles Forever’ (Streeting et al, 2022; http://facebook.com/bellsturtles) programmes, advocates that the future is looking brighter for Australia's freshwater turtles.…”
Section: Discussionmentioning
confidence: 99%
“…Conservation biologists continue to refine the best approaches to counteract population declines and causes of mortality in Australian freshwater turtles. Actions include attempts to mitigate threats of feral species such as pigs and foxes through predator‐proof fencing (Cochrane, 2006; Streeting et al, 2023), nest protection measures (Campbell et al, 2020; Connell, 2018;Streeting et al, 2023; Terry et al, 2023), and artificial incubation of eggs and release of hatchlings (Streeting et al, 2022). Likewise, conservation translocations of Critically Endangered species such as reintroductions ( Myuchelys georgesi ) and assisted colonization ( Pseudemydura umbrina ) have attempted to mitigate critically low population sizes due to disease (Chessman et al, 2020) and habitat loss and degradation (Bouma et al, 2020; Kuchling et al, 2018).…”
Section: Priorities and Challenges For The Conservation Of Australian...mentioning
confidence: 99%